6-Phosphogluconate Dehydrogenase Links Cytosolic Carbohydrate Metabolism to Protein Secretion via Modulation of Glutathione Levels. Issue 9 (19th September 2019) - Li, Haoxin; Ericsson, Maria; Rabasha, Bokang; Budnik, Bogdan; Chan, Sze Ham; Freinkman, Elizaveta; Lewis, Caroline A.; Doench, John G.; Wagner, Bridget K.; Garraway, Levi A.; Schreiber, Stuart L.
Summary: The proteinaceous extracellular matrix (ECM) is vital for the survival, proliferation, migration, and differentiation of many types of cancer. However, little is known regarding metabolic pathways required for ECM secretion. By using an unbiased computational approach, we searched for enzymes whose suppression may lead to disruptions in protein secretion. Here, we show that 6-phosphogluconate dehydrogenase (PGD), a cytosolic enzyme involved in carbohydrate metabolism, is required for ER structural integrity and protein secretion. Chemical inhibition or genetic suppression of PGD activity led to cell stress accompanied by significantly expanded ER volume and was rescued by compensating endogenous glutathione supplies. Our results also suggest that this characteristic ER-dilation phenotype may be a general marker indicating increased ECM protein congestion inside cells and decreased secretion. Thus, PGD serves as a link between cytosolic carbohydrate metabolism and protein secretion. Graphical Abstract: Highlights: Compounds targeting distinct protein secretion steps might cause similar phenotypes PGD is a link between cytosolic carbohydrate metabolism and protein secretion PGD suppression leads to ER dilation by modulating GSH levels ER dilation is a marker of increased ECM protein congestion and decreased secretion Abstract : Li et al. discovered 6-phosphogluconate dehydrogenase (PGD) as a link between cytosolic carbohydrate metabolism and protein secretion. By showing that PGD suppression causes a characteristic ER-dilation phenotype that is associated with increased ECM protein inside cells as well as decreased secretion, the authors propose a "congestion-to-dilation" model.